The Protective Effects of Bushen Daozhuo Granule on Chronic Non-bacterial Prostatitis - Sun, Dalin; Xing, Dong; Wang, Dandan; Liu, Yuanyuan; Cai, Bin; Deng, Weimin; Hu, Qinglin; Ma, Wenjun; Jin, Baofang (Frontiers in Pharmacology, 2024)
Background: Chronic non-bacterial prostatitis (CNP), one of the most common chronic diseases in urology, leads to pain in the prostate and dysuria, critically affecting the physical or mental health of patients. However, there are no standard treatment approaches for the treatment of CNP in the clinic. Although the clinical application of Bushen Daozhuo granule (BSDZG) offers hope to CNP patients in China, the mechanisms of BSDZG in treating CNP are still not entirely clear. Hence, we aimed to investigate the novel therapeutic mechanisms of BSDZG on CNP. Methods: In this study, we first assayed the prostate index of rats and then determined the anti-inflammatory and anti-apoptotic effects of BSDZG on CNP in vivo and in vitro by employing ELISA kits and TUNEL staining. Next, we investigated whether the anti-inflammatory and anti-apoptotic mechanisms of BSDZG on prostate protein-induced rats and lipopolysaccharide (LPS) induced RWPE-1 cells were related to the AKT, p38 MAPK, and NF-κB pathways with the help of Western blot. Finally, the influence of BSDZG on the interaction between the p38 MAPK and NF-κB pathway in LPS-induced RWPE-1 cells was explored by adopting dehydrocorydaline (DHC, p38 MAPK activator) with the help of ELISA kits and Western blot. Results:In vivo, BSDZG effectively reduced the prostate index. In vivo and in vitro, BSDZG dramatically declined the level of two pro-inflammatory cytokines, TNF-α and IL-1β, as well as the apoptosis rate. Moreover, in vivo and in vitro, BSDZG memorably upregulated the expression level of p-AKT, and substantially downregulated the expression level of p-p38 MAPK and NF-κB2. The activation of p38 MAPK significantly reversed the moderation effects of BSDZG on the level of TNF-α and IL-1β, as well as the expression level of p-p38 MAPK and NF-κB2 in vitro. Conclusion: To sum up, the in vivo and in vitro therapeutic mechanisms of BSDZG on CNP were reflected as the anti-inflammation and anti-apoptosis that was formed by inhibiting the level of pro-inflammatory cytokines, TNF-α and IL-1β, to regulate the AKT, p38 MAPK, and NF-κB pathways, and the anti-inflammatory effect of BSDZG was realized by suppressing the p38 MAPK pathway to inhibit the downstream NF-κB pathway.